2017
DOI: 10.1002/ajmg.a.38199
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 deletion syndrome in diverse populations

Abstract: 22q11.2 deletion syndrome (22q11.2 DS) is the most common microdeletion syndrome and is underdiagnosed in diverse populations. This syndrome has a variable phenotype and affects multiple systems, making early recognition imperative. In this study, individuals from diverse populations with 22q11.2 DS were evaluated clinically and by facial analysis technology. Clinical information from 106 individuals and images from 101 were collected from individuals with 22q11.2 DS from 11 countries; average age was 11.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 28 publications
3
100
0
6
Order By: Relevance
“…This difference in phenotype may be due to a combination of recognition bias and referral bias. Recognition bias is due to the possibility that facial features are distinct in different populations as has been demonstrated in other syndromes (Kruszka, Addissie, et al, ; Kruszka, Porras, Addissie, et al, ; Kruszka, Porras, Sobering, et al, ; Kruszka et al, ) and as such the facial gestalt in BWS may be under‐diagnosed in non‐Caucasian groups. Secondly, referral bias may exist in that non‐Caucasian patients with BWS may be less frequently referred to a tertiary care center due to socioeconomic stratification and/or other barriers to care and follow‐up, resulting in only the extreme cases such as hyperinsulinism being referred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in phenotype may be due to a combination of recognition bias and referral bias. Recognition bias is due to the possibility that facial features are distinct in different populations as has been demonstrated in other syndromes (Kruszka, Addissie, et al, ; Kruszka, Porras, Addissie, et al, ; Kruszka, Porras, Sobering, et al, ; Kruszka et al, ) and as such the facial gestalt in BWS may be under‐diagnosed in non‐Caucasian groups. Secondly, referral bias may exist in that non‐Caucasian patients with BWS may be less frequently referred to a tertiary care center due to socioeconomic stratification and/or other barriers to care and follow‐up, resulting in only the extreme cases such as hyperinsulinism being referred.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of diversity in malformation syndromes has recently arisen as an important topic for both diagnosis and management of patients. Studies using facial analysis technology have revealed subtle differences in the facial appearance between racial groups in patients with Down syndrome, 22q syndrome, Noonan syndrome, and Williams–Beuren syndrome (Kruszka, Addissie, et al, ; Kruszka, Porras, Addissie, et al, ; Kruszka, Porras, Sobering, et al, ; Kruszka et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We describe a novel IGF2 splice site pathogenic variant in a child with SRS, the first to be described in an Australian Aboriginal girl adding to the body of literature on the phenotype associated with IGF2 pathogenic variants. For global health equity, it is critical to report the phenotype of rare conditions within and between diverse populations (Kruszka et al, ). We expand on the phenotype by displaying the facial photographs (Figure ), to assist in diagnosing further Aboriginal and Non‐Aboriginal children via raising awareness of the clinical cues important for prompting consideration of further diagnostic investigations (Wakeling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, adults with CHD should undergo an equivalent evaluation by an adult congenital heart disease specialist or medical geneticist. Facial analysis technology is becoming a useful tool to assist both the geneticists and nongeneticists (Kruszka, Addissie, et al, ; Kruszka, Porras, et al, ; Kruszka, Porras, Sobering, et al, ; Kruszka et al, ; Kruszka et al, ). This tool is especially significant given the shortage of trained medical geneticists (Maiese, Keehn, Lyon, Flannery, & Watson, ).…”
Section: Approach To Genetic Testingmentioning
confidence: 99%